A GENERATIVE CAD MODEL OF A WORM GEAR MESHING - Angelika WRONKOWICZ; Dominik WACHLA (Scientific Journal of Silesian University of Technology. Series Transport)
This article introduces the term of a generative CAD model, its origins and, thus, a need of creating such a type of models. A process of generative model creation as well as specific forms of knowledge recording applied in the implementation phase in various CAD systems are briefly discussed. The example of a worm gear meshing realized by the CATIA software encapsulates the methodology of generative model construction. Sources and types of knowledge for design and construction required for development of the aforementioned model as well as the UML language as a method of formal knowledge recording are presented. The concept of model creation, i.e. assumptions and the structure as well as logic of the model operation are described. Also, the paper addresses selected elements of the project that present the manner in which the model was constructed.